2023
DOI: 10.1001/jamanetworkopen.2023.23289
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Ultrasonography-Based Risk Models in Differentiating Between Benign and Malignant Ovarian Tumors in a US Cohort

Abstract: ImportanceUltrasonography-based risk models can help nonexpert clinicians evaluate adnexal lesions and reduce surgical interventions for benign tumors. Yet, these models have limited uptake in the US, and studies comparing their diagnostic accuracy are lacking.ObjectiveTo evaluate, in a US cohort, the diagnostic performance of 3 ultrasonography-based risk models for differentiating between benign and malignant adnexal lesions: International Ovarian Tumor Analysis (IOTA) Simple Rules with inconclusive cases rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…We reviewed the remaining 134 full-text articles, and 122 were excluded for reasons as follows: insufficient data to determine diagnostic performance ( n = 23) and not in the field of interest ( n = 99). Finally, a total of 12 studies were included in this meta-analysis ( 20 31 ). The flowchart of the literature selection process is demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We reviewed the remaining 134 full-text articles, and 122 were excluded for reasons as follows: insufficient data to determine diagnostic performance ( n = 23) and not in the field of interest ( n = 99). Finally, a total of 12 studies were included in this meta-analysis ( 20 31 ). The flowchart of the literature selection process is demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For this meta-analysis, all the studies included had a retrospective study design, with eight studies reporting a head-to-head comparison between O-RADS and the ADNEX model ( 21 , 23 28 , 31 ) and seven studies reporting a direct comparison between O-RADS and IOTA SR (including three studies performing a comparison between all three guidelines) ( 20 , 22 , 23 , 25 , 29 31 ). The study sample ranged from 122 to 1,179 patients, with an average age of 35–52.3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the rst multiclassi cation model that consists of three clinical indexes and six ultrasonic indexes [13]. A previous study demonstrated that the ADNEX model showed diagnostic performance for identifying adnexal lesions [14,15]. However, no studies have reported the validation of the ADNEX model in epithelial ovarian tumors.…”
Section: Introductionmentioning
confidence: 99%